Pengaruh Pengelasan dan Media Quenching Terhadap Kekuatan Tarik dan Kekerasan Material ASTM A 36 - Hamdani Hamdani; Jufriadi Jufriadi; Ariefin Ariefin; Edi Saputra; Mohd. Ghiffari (Jurnal Teknologi, 2021)
In this study the tensile strength and hardness of ASTM A36 material that weld by SMAW process with variations in cooling media, namely seawater, air, and oil. The highest tensile strength value is 81.16 Kgf/mm2 with seawater cooling media. The highest hardness value in the base metal area is 93.5 HRC with oil cooling treatment. The highest hardness value in the weld metal on specimens using air cooling treatment is 93.33 HRC. The highest hardness value in the HAZ area is in the specimens using seawater cooling treatment with a value of 90.83 HRC. The Phase change during quenching proses with different media probably affects the mechanical properties of ASTM A36 material.